Pengaruh Perencanaan Pajak Perusahaan, Pertumbuhan Perusahaan dan Pajak Tangguhan Terhadap - Muhammad Excel Nugraha; Wulandari Cahyani Putri (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the influence of corporate tax planning, company growth and deferred taxes on earnings manajement. This research was conducted on 46 Food and beverages Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2018 - 2022. The sampling technique uses purposive sampling, so that there are 20 companies as samples with a total of 100 data processed. The results of this research show that corporate tax planning, company growth and deferred taxes simultaneously influence profit manajement. Partially, corporate tax planning has no effect on earnings manajement. Company growth influences profit manajement. Deferred Tax has no effect on earnings manajement